Beneficiation of municipal glass packaging waste as a secondary flux for ceramic tile production - Baran, Ece; Dinc, Nazlim Ilkyaz; Burat, Firat (ELSEVIER SCI LTD, 2026)
This study examines the recovery and reuse of glass packaging waste from municipal solid waste as a sustainable raw material for ceramic tile production. Waste glass was processed through comminution, shaking table separation, and froth flotation to remove mineral impurities, lightweight organics, and fine contaminants. The optimized collector-free flotation route produced a glass-rich concentrate containing 73.54 wt% SiO2 and 0.49 wt % loss on ignition (LOI) at a mass recovery of 83.2%, confirming the efficiency of the beneficiation stage. The upgraded glass was incorporated into a reference ceramic tile body at different addition levels and fired at 1150, 1170, and 1200 degrees C. Results showed that 5 wt% glass enabled full vitrification at 1170 degrees C, achieving flexural strength of 78.5 MPa and water absorption of 0.031%. This performance was comparable to the reference body fired at 1200 degrees C, demonstrating that recycled glass can reduce firing temperature by approximately 30 degrees C without compromising technical properties, while contributing to lower energy consumption and associated CO2 emissions. Higher additions (>= 7.5 wt%) increased water absorption and slightly reduced strength, highlighting the importance of dosage optimization. Overall, the study confirms that beneficiated waste glass can function as an effective fluxing raw material for ceramic tiles, reducing energy demand, diverting waste from landfill, and supporting circular economy and low-carbon manufacturing strategies. Future work will focus on pilot-scale validation of the collector-free flotation route, direct microstructural characterization of fired ceramic bodies, and life-cycle assessment of the integrated process.
Keywords: Waste glass; Froth flotation; Ceramic tiles; Recycling; Circular economy; Materials Science